If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11m + 1 = 8m + 4 Reorder the terms: 1 + 11m = 8m + 4 Reorder the terms: 1 + 11m = 4 + 8m Solving 1 + 11m = 4 + 8m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-8m' to each side of the equation. 1 + 11m + -8m = 4 + 8m + -8m Combine like terms: 11m + -8m = 3m 1 + 3m = 4 + 8m + -8m Combine like terms: 8m + -8m = 0 1 + 3m = 4 + 0 1 + 3m = 4 Add '-1' to each side of the equation. 1 + -1 + 3m = 4 + -1 Combine like terms: 1 + -1 = 0 0 + 3m = 4 + -1 3m = 4 + -1 Combine like terms: 4 + -1 = 3 3m = 3 Divide each side by '3'. m = 1 Simplifying m = 1
| 6y-2=4y+14 | | 3(x+5)+5+1=31 | | -2(4x-9)=10 | | 12x-4+x=180 | | 9d^2+3d-5=0 | | 8(3m-2)=104 | | 41=6v-7 | | 42y-42y^2=20 | | (2x-1)(x+2)+(3x+1)(x-1)= | | 3(n+4)-8=11-(6-2n)52 | | 3*(2x-1)=9 | | 8x-2y=60 | | 7/(10x)=103/20 | | 4x=8x+32 | | x-0.7=5.5 | | 7x3/6 | | x*2x=50000 | | 3(2b-1)=27 | | 1/8x-1/8y=19 | | log(12)2+log(12)x=log(12)(x+7) | | 2x^3+12=0 | | -7-13=15 | | -4x+2y=34 | | 2x+7=-3x+8 | | (4x+7)=(7x-8) | | (6a^4b^3)(3ab^2)= | | X-4+12=12-2 | | 6xy*xy*4y= | | 2(4y-2)= | | (x+3)+(x-3)=1 | | (x+3)+(x-3)=0 | | 6(y+9)-56= |